Do'a Poma Home Industry Development Through Improved Managerial Knowledge and Product Packaging Innovation: Pengembangan Industri Rumah Tangga Do’a Poma Melalui Peningkatan Pengetahuan Manajerial dan Inovasi Kemasan Produk - Desy Puspita; Nurmalia Zakaria; Indra Akbar; Safrizal Razali; Yanti Saftini (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2024)
Do'a Poma snack business is one of the home industries whose members are housewives from poor families in Aceh Besar. The business problems faced are low marketing, no business legality and financial bookkeeping, and low quality packaging. This community service activity aims to optimize and develop the Do'a Poma Home Industry (IRT) business through financial bookkeeping, marketing, and product packaging improvement training. This program is expected to improve the skills and knowledge of IRT Do'a Poma business actors in managing their businesses more professionally and competitively. The training was carried out in the form of workshops, mentoring and evaluation. Participants were actively involved in simulations and interactive discussions to ensure that they could directly apply the results of the mentoring in their daily business activities. The results of this activity showed a significant increase in participants' abilities in preparing financial reports, creating a better marketing system by providing four variants of banana chip flavors, and more attractive and safe product packaging. This community service activity went very well and was right on target.